What's new in biopotential of fruit and vegetable by-products applied in the food processing industry. (September 2017) - Kowalska, Hanna; Czajkowska, Kinga; Cichowska, Joanna; Lenart, Andrzej
Abstract: Background: According to the data on global fruit and vegetable production, the amount of residue with potential utilization after processing has been estimated in millions tons every year. This involves the use of various forms of energy, water and other factors. Of greatest importance is the by-product potential because of the content of biocomponents, which may be used for innovative food production. Appropriate actions should be taken to transform by-products into valuable products because of their abundant natural compounds. Scope and approach: The aim of this work was to review current trends in solving the problem of waste produced by the processing of plant raw materials. Due to the high content of bioactive components, by-products( peel, pulp, seeds) constitute a natural raw material for the recovery of valuable nutrients, such as polyphenols or aromatic oil. The extracted substances may be used in the food production as functional ingredients and nutraceuticals or in cosmetic and pharmaceutical industries. It is possible to enrich food with health-promoting ingredients. Key findings and conclusions: Modern sustainable food processing technology should keep in mind the need to reduce by-products and use their potential effectively. The impact of these actions is important for the current food economy, as well as the future state of the environment. Still, too few residues from the processing of fruit and vegetables are used appropriately in the food industry as new attractive with natural ingredients enriching food and in the pharmaceutical field, biofuel production and others. Graphical abstract: Highlights: Fruit and vegetable by-products are rich source of bioactive substances. It is necessary to develop the strategy of the use of by-products potential. Components from by-products are good source for food enrichment or supplements. Components from by-products are good source for animal feed.